The Influence of School Culture on the Character Education of Class IV Primary School Students - Vinona, Gracia; Silaban, Patri Janson; Sipayung, Regina; Gaol, Rumiris Lumban; Wulansari H.S, Dyan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This study aims to determine the effect of school culture on the character education of fourth grade students at SD Negeri 060903 Medan Helvetia. The independent variables in this study are school culture (X) and the dependent variable character education (Y). The method used in this research is a quantitative survey type approach, the sample in this study is 39 students from all grades IV. Data on school culture and character education were obtained from a questionnaire distributed to fourth grade students. Student character education shows that the average value of students is 79.1. Furthermore, the normality test results are at a significant level (α = 0.05) with normal criteria, namely Lcount ≥ Ltable. From the results of school culture, the Lcount value is greater than the Ltable value where Lcount is 0.200 ≥ 0.05 Ltable, so school culture is normally distributed. From the analysis results with SPSS ver 22, a correlation coefficient of 0.857 is obtained, meaning rcount ≥ rtable, so there is an influence of school culture on character education. In the t test conducted, namely tcount ≥ ttable and the results obtained were 10.09 ≥ 1.687, which means that Ha is accepted and H0 is rejected, so there is an influence between school culture on the character education of class IV students at SD Negeri 060903 Medan Helvetia in the 2022/2023 Academic Year.